Technical report: Postharvest Physiological Deterioration (PPD) tolerance of selected Ugandan cassava varieties. Extending the shelf-life of fresh cassava roots for increased incomes and postharvest losses reduction - Muyinza, H.; Nuwamanya, E.; Wanda, K.; Waigumba, S.P.; Kwagala, I.; Nyamutoka, P.; Menya, G.; Aceng, S.; Nyakaisiki, E.; Kaliisa, R.; Abass, A.; Matovu, Moses (2016)
The purpose of this study is to screen cassava varieties for their level of tolerance or susceptibility to Postharvest Physiological Deterioration (PPD). Specifically, it aims at collecting varieties of fresh cassava roots preferred by consumers in Ugandan. The study targets the two major fresh cassava supply axes, i.e., Masindi/Kiryandongo and Kyenjojo/Kabarole. Fresh cassava roots were screened for tolerance or susceptibility to PPD. The study also aims at determining the effect of pruning on the deterioration of cassava roots over time and the changes in root biochemistry during storage of both pruned and non-pruned cassava varieties.